2017
DOI: 10.3390/su9071259
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Greenbelt Policies on Land Development: Evidence from the Deregulation of the Greenbelt in the Seoul Metropolitan Area

Abstract: Greenbelt policies are important urban containment policies. On the one hand, they can effectively control the disorderly growth of a city; on the other hand, they can cause other social problems because of their strict control over land development. This paper uses data from 2000 and 2010 and the difference-in-differences (DID) method to evaluate the effects of greenbelt deregulation policies on urban land development in the Seoul metropolitan area (SMA) through a quasi-natural experiment. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 45 publications
3
12
0
4
Order By: Relevance
“…Recently, some research has focused on the effects of partially relaxing the GB restriction on land development in the case of the Seoul metropolitan area [35,36]. The latter study [36] found that the GB deregulation had significant effects on urban land development near the boundary of the city of Seoul and the GB boundary.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, some research has focused on the effects of partially relaxing the GB restriction on land development in the case of the Seoul metropolitan area [35,36]. The latter study [36] found that the GB deregulation had significant effects on urban land development near the boundary of the city of Seoul and the GB boundary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, some research has focused on the effects of partially relaxing the GB restriction on land development in the case of the Seoul metropolitan area [35,36]. The latter study [36] found that the GB deregulation had significant effects on urban land development near the boundary of the city of Seoul and the GB boundary. Similarly, Han [35] also found that the GB relaxation served to guide new development to the inner areas of the GB while slowing down the rates of development beyond the GB.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations